Climate, security, and the study of religion in Africa: Insights from Northern Mozambique - Tarusarira, Joram; Maviza, Gracsious (2025)
How the security risks associated with climate change, such as social instability and conflicts over dwindling resources, impact the study of religion in Africa has received limited attention from scholars of African religions, despite the need to determine how these impacts influence how religion is conceptualized. However, climate-related security risks intersect with religious beliefs and practices. This article draws on participatory methodologies and an ethnographic study of the security risks stemming from climate change in northern Mozambique. It demonstrates that the emergence of security challenges related to climate change provides religious studies with new data and, therefore, new challenges in rethinking the meaning of African religions. It also shows the significance of attributing religion to climate disasters among religious communities, exposes the epistemological assumptions and conflicts over the role of religion in social challenges, and demonstrates the transcendence of religious differences in times of widespread social crises. The article thus contributes to setting the stage for future studies that aim to understand how climate-driven vulnerabilities change the conception of and engagement with religion in Africa.